LAND, LAW, AND JUSTICE: INDONESIA'S CRUSADE AGAINST LAND GRABBING IN THE ERA OF THE NEW CRIMINAL CODE - Agusalim; Zico Junius Fernando; Ganefi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This research examines the intricate issues of land grabbing and agrarian conflicts in Indonesia, spotlighting the socio-economic and legal challenges faced by local communities, smallholders, and indigenous peoples. Utilizing a normative legal methodology, the study delves into statutory, conceptual, and futuristic approaches to analyze the phenomenon of land grabbing, which has been exacerbated by global food demand, economic interests, and the expansion of capitalism. The enactment of Law No. 1 of 2023 on the new Criminal Code (KUHP) in Indonesia marks a pivotal development in addressing crimes against land, offering robust legal protection against land dispossession, and ensuring equitable land transactions. The research underscores the dire need for agrarian reform, rooted in the principles of the Basic Agrarian Law (UUPA) and aimed at rectifying the unequal distribution of land. It argues for a balanced approach that harmonizes the interests of society, including marginalized groups, with those of investors to foster sustainable development and social justice. The study highlights the legislative efforts to tackle land-related crimes through the new KUHP, emphasizing the significance of transparency, fairness, and the protection of legal rights in land management. Through a comprehensive analysis, this research contributes to the discourse on sustainable national development, advocating for policy reforms and legal measures to combat land grabbing. It calls for a more democratic policy-making process, involving civil society's active participation, to ensure equitable land distribution and uphold the welfare of smallholders and indigenous peoples.